Disfunción inmunometabólica en el VIH: bases epistemológicas - Gutiérrez-Salas , A. A.,; Delgadillo-Guzmán, D.,; Hernández-Silva, M.,; López-Márquez , F. C., (Revista de Ciencias Médicas Torreón, 2026)
The relationship between metabolic syndromeand proinflammatory cytokines in people living with HIV hasnot been conclusively established. It is suggested that chronicinflammation, derived from viremia and metabolicalterations, could explain this association. This articleproposes an epistemological reflection aimed atstrengthening scientific understanding and the application ofbioethics in future epidemiological research. Materials andmethods: A qualitative study was conducted with ahermeneutic and epistemological approach. A documentaryand critical analysis of scientific articles, systematic reviews,and regulatory documents related to HIV, cytokines, andmetabolic syndrome was performed. Results: The analysisallowed us to identify patterns and ethical andepistemological implications in the reviewed literature. Theideas of David Hume on experience-based knowledge andBradford Hill on the criteria of causality in epidemiology aretaken up as references for the construction of scientificknowledge. In conclusion, the integration of philosophicaland bioethical thought into medical research allows us toreinterpret knowledge from a humanistic perspective,recovering lessons from the past to guide science toward amore reflective, ethical, and socially responsible practice
Keywords: Ocimum basilicum L., eugenol, natural repellent, stability, Aedes aegypti.